Dominance of community-associated methicillin-resistant Staphylococcus aureus clones in a maternity hospital - Udo, Edet E.; Al-Sweih, Noura (PLOS ONE, 2017)
Background Methicillin- resistant Staphylococcus aureus (MRSA) is a major pathogen causing healthcare- and community- acquired infections. The purpose of this study was to characterize MRSA isolated at the Maternity Hospital between 2006 and 2011 for their genetic relatedness. Materials and methods The MRSA isolates were investigated using a combination of antibiogram, Staphylococcal chromosome cassette mec (SCCmec) and spa typing to determine their relatedness to MRSA isolated in other Kuwait hospitals. The isolates were also investigated for the carriage of genes for Pantone valentine Leukocidin (PVL). Results A total of 103 MRSA obtained from 64 neonates, 17 adult patients and 12 healthcare workers. The isolates were resistant to Kanamycin (46.6%), gentamicin (40.8%), trimethoprim (32%), ciprofloxacin (22.3%), fusidic acid (16.5%), tetracycline (19.4%), erythromycin (15.5%), clindamycin (15.5%), streptomycin (11.6%) high-level mupirocin (2.9%) and chloramphenicol (0.9%). Twenty (19.4%) of the isolates were multiresistant. Thirty-one (30.0%) isolates were positive for PVL. Molecular typing revealed the presence of 11 clonal complexes and 23 clones with ST5-V-t002, (N = 22), ST22-IV-t223 (N = 18), ST22-IV-t852 (N = 10), ST80-IV-t044 (N = 7), ST5-V-t688 (N = 5), ST772-V-t657 (N = 5) and ST239-III-t860 (N = 4) constituting 66.9% of the isolates. Other clones were isolated sporadically. The number of MRSA isolates increased from two in 2006 to 22 in 2011 with a peak of 43 in 2008. Conclusion The study revealed a high prevalence of community-associated MRSA Maternity hospital. The MRSA population consisted of known strains, such as ST239-III-t680, ST22-IV-t223/t852 and ST80-IV-t044, that were reported previously in Kuwait and novel strains such as ST5-V-t002, and several sporadic strains obtained for the first time in the Maternity hospital. This study has provided an initial data which will serve as a platform for future comparative studies on the distribution of MRSA clones in the Maternity hospital in Kuwait.